(untitled) (Historia, 2021)
The South African War forced M. Gandhi to reassess his political strategy and loyalty to Empire. During the 1890's Indians were subject to a battery of racist legislation in Southern Africa. When the Boer republics declared war on Britain, Gandhi saw this as a perfect opportunity to prove Indian loyalty to the Empire. Although elite Indians offered their services without pay, the Government accepted their help with great reluctance. The blatantly racist attitude of the Natal Government before and during the war, and the British policy of allowing whites to subjugate Indians politically and economically during the post-war period, made Gandhi understand the second-class status of the colonised. In response he developed his technique of satyagraha and lost faith in an empire embracing both coloniser and colonised.